Comprehensive metagenomic insights into a unique mass gathering and bathing event reveals transient influence on a riverine ecosystem - Yadav, Rakeshkumar; Rajput, Vinay; Gohil, Kushal; Khairnar, Krishna; Dharne, Mahesh (Ecotoxicology and Environmental Safety, 2020)
The religious mass gathering and bathing can pose a multitude of significant public health challenges and lead to severe alterations in the river microbial ecology. The Pandharpur Wari is an annual pilgrimage of Maharashtra, India, where millions of devotees carry the footprints of the saint-poets and pay their obeisance to Lord Vitthal on the 11th day of moon's waxing phase (Ashadi Ekadashi). As a part of the ritual, the engrossed devotees, walk over 250 km, take a first holy dip in a sacred river Indrayani at Alandi and secondly in Bhima River at Pandharpur. The MinION-based shotgun metagenomic approach was employed to examine the impact of spiritual mass bathing on environmental changes (concerning the river microbial community structure and functions); and public health aspects (in terms of changes in the pathogenic potential and antibiotic resistance). The analysis of bathing and post-bathing samples of both the rivers revealed alterations in the alpha and beta diversity, indicating significant spatiotemporal variations in the overall microbial structure and function. Furthermore, the analysis revealed up to 80% of differences in the abundance of virulence genes between the bathing and post bathing samples. We observed parallel increase of priority skin and enteric pathogens (ranging from 11% to 80%) such as Acinetobacter baumannii, Staphylococcus aureus, Streptococcus pyogenes, Mycobacterium tuberculosis, and Pseudomonas aeruginosa during the bathing event. Moreover, we observed a significant increase in the antibiotic resistance in the bathing samples of Bhima and Indrayani rivers respectively. Altogether, this is the first comprehensive metagenomic study unravelling the influence of religious mass-bathing on the riverine ecosystem.
Keywords: Antibiotic resistance; Mass bathing; MinION sequencing; Priority pathogens; Virulence genes